Knowledge and attitudes of junior high school and high school students towards first aid - Olchawa, Joanna; Fecko - Gałowicz, Kinga (Nursing Problems / Problemy Pielęgniarstwa, 2017)
Introduction The ability to provide first aid for accidental bystander is very important.. Target work The aim of the study was to investigate the level of knowledge and attitudes of junior high school and high school students towards first aid given to the injured. Material and methods The study involved 175 subjects, including third grade students of junior high school and students of final year of secondary school that were randomly selected. The study used the author prepared a questionnaire, which was distributed to the classroom hours of education in the two types of schools. The statistical calculations use has the chi-square test. For each test assumes significance level equal to 0.05. Results Young people attend first aid trainings both at school and in the classes organized by school. In the vast majority they know the emergency numbers and show a willingness to further training, however they did not show willingness to educate themselves on the medical professions. The results of the questions concerning first aid were quite well. The problem, however, were the response from the scope of the control of hemorrhage, assistance in case of burning clothes and dealing with unconscious. Conclusions Knowledge of first aid secondary school students and secondary school pupils drew mainly from activities conducted on school grounds. The level of knowledge should be assessed as satisfactory. The exception is the inability to conduct a bleeding, unconscious and with oparzonym burning clothing. Older (high school) youth more frequently gave correct answers than secondary school students.